Plasma cell proliferation in monoclonal gammopathies: measurement using BU-1 antibody in flow cytometry and microscopy: comparison with serum thymidine kinase. Issue 5 (May 1995) - Schambeck, C M; Wick, M; Bartl, R; Lamerz, R; Fateh-Moghadam, A
Abstract : AIMS--The labelling index as defined by the percentage of bone marrow plasma cells doubling their DNA in the S phase is a useful prognostic factor in multiple myeloma. The aim of this study was to examine the specificity and sensitivity of a new flow cytometric method for measuring the labelling index. METHODS--Bone marrow specimens from five patients with monoclonal gammopathy of undetermined significance and 61 patients with multiple myeloma were investigated. The labelling index (LI%) was determined by means of a microscopic and flow cytometric method using the antibromodeoxyuridine antibody BU-1. Serum thymidine kinase, another index of proliferation, was measured by radioimmunoassay. RESULTS--Good comparability (r = 0.83) and nearly equal imprecision (CV < 20%) were found with microscopic and flow cytometric methods of LI% measurement. However, 1000 or more cells had to be counted by microscopy around the cutoff value to avoid an unacceptable imprecision. Plasma cells with increased S phase (LI% > 1%) were characterised by their reduced light chain fluorescence intensity ratio between plasma cells and nonspecifically stained cells (7.9 v 14.8, p < 0.002), that is, by their generally lowered cytoplasmic immunoglobulin content. There was a moderate correlation between thymidine kinase and labelling index (r = 0.56, p < 0.001). At 100% specificity, myelomas with proliferating plasma cells were more sensitively detected by the labelling index than by serum thymidine kinase (55% v 32% sensitivity). CONCLUSIONS--The labelling index represents a more specific and sensitive proliferation marker than serum thymidine kinase. Flow cytometry does not result in greater precision.